Immigration en France : garanties et risques des procédures administratives et judiciaires dématérialisées. Migration et e-administration en France .......... 13 - Mengès-Le Pape, Christine (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
IMMIGRATION TO FRANCE: GUARANTEES AND RISKS OF DEMATERIALIZED ADMINISTRATIVE AND JUDICIAL PROC EDURES: MIGRATION AND E-GOV ERNMENT IN FRANCEForeigners’ rights are a major concern for French and European legislators. In France, reforms have followed one another for over twenty years, culminating in the recent “bill to control immigration and improve integration” of February 2023. The density of the French legal text has made the rules so complex that both users and prefectures are hampered by them. Under the cover of a good administration developed to remedy the regulatory labyrinth, administrative and legal procedures have been dematerialised possibly supported by algorithms and artificial intelligence. A remote digital administration service (ANEF) has been set up, and the use of video hearings to keep foreign nationals in detention has become commonplace. However, these new practices aimed at managerial efficiency run the risk of stripping the administration of its traditional values and undermining users’ rights. French case law, in particular the Council of State’s ruling of 3 June 2022, has expressed concern about these developments, which are subject to managerial logic and can only lead to a deterioration in the reception of foreign nationals.